Safety and clinical outcomes of orelabrutinib, lenalidomide plus sintilimab for relapsed/refractory diffuse large B-cell lymphoma - Wang, Lingling; Huang, Yongfen; Xu, Dan; Wang, Xiaoyong; Chu, Hailiang; Wang, Chunling; Xu, Hao; Sang, Wei; Cheng, Yuexin; Miao, Yuqing (Frontiers in Immunology, 2025)
IntroductionThis study evaluated the safety and clinical outcomes of orelabrutinib, lenalidomide plus sintilimab in relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL).MethodsThirty-four patients were given orelabrutinib 150 mg once daily, lenalidomide 25 mg once daily on days 1–10, and sintilimab 200 mg intravenously on day 1 of each 21-day cycle.ResultsWith a median follow-up of 9 months (95% CI, 8.3-9.6), 7 patients died. The 1-year progression-free survival (PFS) and overall survival (OS) were 41.9% and 77.8%, respectively. The median PFS was 6 months (95% CI, 3.4-8.6), and median OS was not reached. The median exposure time was 4 months, while the median time to first response was 2 months. The best objective response rate (ORR) was 58.8%, with a complete remission (CR) rate of 38.2%. Twenty-eight (82%) patients presented with treatment-related adverse events (TRAEs), and 7 (20.6%) patients developed grade 3 or higher TRAEs. The most common grade 1 TRAEs were neutropenia (64.7%), thrombopenia (44.1%), skin rash (32.4%), and fatigue (29.4%). Patients who responded to treatment had a higher proportion of PD1+CD8+ T cells, a lower percentage of CD8+ T cells, and a higher percentage of CD4+ T cells and lower C-reactive protein (CRP) levels at baseline. Cytokines such as IL-6, IL-8, and IL-10 levels were also substantially lowered in these patients.DiscussionOrelabrutinib, lenalidomide plus sintilimab demonstrated promising efficacy and a manageable safety profile in Chinese patients with R/R DLBCL.